2013
DOI: 10.1128/mbio.00398-13
|View full text |Cite
|
Sign up to set email alerts
|

Evolutionary Dynamics of Vibrio cholerae O1 following a Single-Source Introduction to Haiti

Abstract: Prior to the epidemic that emerged in Haiti in October of 2010, cholera had not been documented in this country. After its introduction, a strain of Vibrio cholerae O1 spread rapidly throughout Haiti, where it caused over 600,000 cases of disease and >7,500 deaths in the first two years of the epidemic. We applied whole-genome sequencing to a temporal series of V. cholerae isolates from Haiti to gain insight into the mode and tempo of evolution in this isolated population of V. cholerae O1. Phylogenetic and Ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

13
118
4
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 122 publications
(138 citation statements)
references
References 39 publications
13
118
4
2
Order By: Relevance
“…Whole genome sequence analysis indicated the Haiti isolates were monophyletic with isolates from Nepal, in agreement with a prior hypothesis that the Haiti cholera epidemic arose from a single point source introduction from Southeast Asia (1). Importantly, genome analysis also confirmed that the regulatory and competence apparatus genes of each isolate tested for transformation proficiency were identical to uptake-proficient isolate C6706 (149), although the putative vc0857-0861 pilin-associated genes (20) had not been described at that time. The nature of the defect(s) responsible for the transformation deficiency of the Haiti isolates remains unknown, but such strains have the potential to reveal novel factors or signals that participate in competence regulation or apparatus function in V. cholerae.…”
Section: How Common Is Natural Competence In V Cholerae and Other Visupporting
confidence: 66%
See 1 more Smart Citation
“…Whole genome sequence analysis indicated the Haiti isolates were monophyletic with isolates from Nepal, in agreement with a prior hypothesis that the Haiti cholera epidemic arose from a single point source introduction from Southeast Asia (1). Importantly, genome analysis also confirmed that the regulatory and competence apparatus genes of each isolate tested for transformation proficiency were identical to uptake-proficient isolate C6706 (149), although the putative vc0857-0861 pilin-associated genes (20) had not been described at that time. The nature of the defect(s) responsible for the transformation deficiency of the Haiti isolates remains unknown, but such strains have the potential to reveal novel factors or signals that participate in competence regulation or apparatus function in V. cholerae.…”
Section: How Common Is Natural Competence In V Cholerae and Other Visupporting
confidence: 66%
“…A recent study of a large set of clinical V. cholerae isolates obtained during the cholera outbreak that followed the 2010 earthquake in Haiti found that each V. cholerae isolate tested was defective for natural transformation (149). Whole genome sequence analysis indicated the Haiti isolates were monophyletic with isolates from Nepal, in agreement with a prior hypothesis that the Haiti cholera epidemic arose from a single point source introduction from Southeast Asia (1).…”
Section: How Common Is Natural Competence In V Cholerae and Other Visupporting
confidence: 52%
“…JNEW01000000) clustered with Haiti clinical isolates (Supplemental Figure S1). 30 The tcpA gene was sequenced for a total of six isolates that were tcpA-positive but ctxA-negative by qPCR ( Table 5). The tcpA sequences did not match prototypical El Tor and classical tcpA sequences (Supplemental Figure S2).…”
Section: Resultsmentioning
confidence: 99%
“…These ecological barriers might later be reinforced by genetic barriers, as sequence divergence accumulates between lineages, eventually inhibiting recombination genome-wide (stage 4). Genetic isolation may also develop more quickly if the capacity for recombination is transiently lost, either genetically (e.g., Katz et al 2013) or physiologically (e.g., by modulating expression of recombination and mismatch repair machinery).…”
Section: Stages In the Speciation Spectrummentioning
confidence: 99%